Comparative analysis of the lipid profiles of bovine fast- and slow-type muscles - Heling Li; Xiaofan Tan; Yize Weng; Lei Zhang; Xuehai Du; Dawei Bian; Yangzhi Liu; Songyang Shang; Peng Li; David M. Irwin; Shuyi Zhang; Bojiang Li (Food Chemistry: X)
Lipid molecules are an important component of meat and are the main source of flavor. However, at present the lipid molecules in meat with different muscle fiber types in cattle are not fully understood. We carried out lipid profiling of eight fast-type longissimus dorsi (LD) muscle and eight slow-type psoas major (PM) muscle samples from LYWC (Liaoyu white cattle). A total of 2032 lipid molecules were identified by our lipidomic analysis of these two muscle tissues, and 134 lipid species were identified as differentially abundant lipids (DALs). A correlation analysis showed the close relationship between the DALs identified in the LD and PM muscle. In addition, some DALs are closely associated with meat quality traits and muscle fiber types. This study identifies lipid molecules that differ between meats with different muscle fiber types and provides new insights into the role of lipids in beef quality improvement.